The Socio-Demography, Clinical Characteristics and the Prevalence of Cardiovascular Risk Factors Among a Group of Elderly Hypertensive Patients Followed Up at A Tertiary Care Hospital in Sri Lanka. - Udaya, Ralapanawa; Sampath, Tennakoon; Thilak, Jayalath; Milinda, Bandara; Noorika, Wickramasurendra; Ravinath, Bandara (Journal of Clinical Case Reports and Images, 2017)
Background Hypertension is one of the most prevalent risk factors for myocardial infarction, strokes, congestive cardiac failure and chronic kidney disease (CKD)and its prevalence is significantly higher inthe elderly population. Objectives To assess the demography, various presentations and the prevalence of risk factors among elderly hypertensive patients followed up in a tertiary care hospital in Sri Lanka. Materials and Methods This was a cross sectional descriptive study involving 250 patients whoseage was 60 years or above onantihypertensives for at least 6 months. Results Approximately 65.2% of the study population was female. The mean age was 70.17.Dizziness and chest pain were the most prevalent symptoms.The mean age at first detection was 58.17 years.Mean SBP and DBP were 128.5mmHg and 81.14mmHg respectively. The prevalence of alcohol consumption and smoking among men were 70.1% and 72.4% respectively. Approximately 54.7% were either overweight or obese.Approximately 81.6% females and 41.4% males had a waist circumference ofmore than therisk level with p-value<0.05. Approximately 36% had diabetes mellitus and 27.6% of the patients had at least one parent and 36.8% had at least one sibling diagnosed with hypertension. Approximately 61.3% of the patients hadadequate levels of physical activity while 31.8% had IHD,11.5% had stroke and 3.8% had CKD. Conclusion Dizziness and chest pain were the most disturbing symptoms while abdominal obesity among females,and alcohol consumption and smoking among males were the major risk factors in elderly hypertensive patients
Keywords: Hypertension; Elderly; Prevalence; Demography; Symptoms; Risk factors